2.5D switchable metasurfaces. (June 2023) - Solomonov, Alexander I.; Kushchenko, Olga M.; Shishkin, Ivan I.; Yavsin, Denis A.; Sinelnik, Artem D.; Rybin, Mikhail V.
Abstract: Nowadays, two-dimensional metasurfaces are widely used to control the amplitude, phase, and direction of light. However, such structures do not provide sufficient degrees of freedom, and thus, the fine adjustment of their optical properties is limited. To solve this problem, phase change materials such as GeSbTe are used. This family of materials is attractive for engineering tunable optical elements because of their non-volatile reversible phase transition and pronounced changes of the dielectric permittivity. Besides, the so-called two and a half dimensional (2.5D) metasurfaces introduce an additional degree of freedom. A fabrication of metasurface combining these two approaches and a detailed study of its photonic properties was reported. The arrangement in 2.5D geometry was tailored to match the lattice resonances to the frequency of the magnetic dipoles supported by the metasurface elements to demonstrate the effects related to the interaction between resonances of different origin. The phase change material enables the on/off switching behavior of the complex resonance effect. Highlights: Fabrication 2.5D switchable metasurfaces. On/off magnetic dipole in GST meta-atoms. Control of the lattice resonances with help 2.5D metasurfaces.